Mitigating Chattering Effect in PMSM Speed Regulation Through Enhanced Fixed Time Convergent Controller - Kumar U.S.; Halder S.; Yalla N.; Tolani S.; Das N.; Bittu Sk. (My University, 2025)
The Permanent Magnet Synchronous Motor (PMSM) in the sector of Electric Vehicle (EV) drivetrain contributes a major role with their high maintenance free performance and high torque with better speed control. However, controlling these motors involves the complex control mechanism due to involvement of permanent magnets in the rotor of the motor. Traditional Sliding mode controller (TSMC) works by incorporating infinite domain through asynchronous convergence but results in chattering issues. To counter effects leading to chattering in PMSM, in this paper a Sliding Mode (SM) controller and observer has been proposed using the Fixed Time Convergent (FTC) mathematical model. Firstly FTC sliding mode Controller (FTCSMC) is designed and incorporated into the control for improved speed loop convergence control where the convergence origin is time independent with fixed designed value on initial starting conditions and also justified by Lyapunov method. Then a fixed Time Sliding Mode Observer (FTSMO) designed to compensate the chattering effect of speed loop by controlling the lumped disturbances occurred in PMSM motor and further enhances the flexibility and easiness of the system in the speed control loop. The results engulfed in the paper presents the robustness of the proposed double controller method along with improved stability in speed performance characteristics of the PMSM motor. The validation of the proposed controller topology is completely designed and carried out analysis in the MATLAB software. © 2024 IEEE.